Recruitment dynamics of cognitive control in insomnia. Issue 5 (21st February 2019) - Muscarella, Charlotte; Mairesse, Olivier; Hughes, Gethin; Neu, Daniel; Van den Bussche, Eva
Abstract: Study Objectives: Individuals with insomnia disorder (ID) commonly report complaints of cognitive control functioning. Conversely, both behavioral and neurological evidence supporting subjective cognitive control impairments in insomnia remain remarkably scarce and inconclusive. To investigate this discrepancy, the present study used next to behavioral measures, event-related potentials (ERPs) to assess proactive control and reactive control in insomnia. Methods: Individuals with insomnia disorder ( n = 18) and good sleeper controls (GSC; n = 15) completed the AX-continuous performance task, while electroencephalography (EEG) was recorded. This task required participants to maintain specific cue-information active to prepare an adequate response to a subsequent probe, which allowed us to measure participants' reliance on both proactive and reactive control. Results: The results indicate that, although ID show a comparable level of performance as GSC, they show a reduced proactive engagement of cue-induced maintenance and response preparation processes (as reflected by the P3b and the contingent negative variation components). Moreover, in contrast to GSC, ID fail to engage reactive control (as indexed by the P3a component) to overcome invalid response tendencies. Conclusions: This study provides neurological evidence for impairments in cognitive control functioning in insomnia. As such, our study contributes to a better understanding of the discrepancy between the commonly reported cognitive impairments in insomnia and the scarce objective evidence supporting these cognitive complaints.